2020
DOI: 10.1177/1354066120902503
|View full text |Cite
|
Sign up to set email alerts
|

Shifting targets: the effect of peacekeeping on postwar violence

Abstract: Existing research shows that peace after civil wars is more stable with peacekeepers present. Yet, violence persists in many postwar contexts, and although postwar violence is often strategic and closely linked to the faultlines of the preceding war, we know little about the impact of peacekeepers on such violence. What we know, moreover, focuses on the former combatants, while this study shows that the majority of deaths in postwar violence are inflicted by other armed actors. This is a challenge for peacekee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
0
21
0
2
Order By: Relevance
“…Specifically, investigating election-related activities helps us to understand how PKOs can secure political transitions after war and nuances general critiques of liberal peacekeeping (for an overview, see Paris, 2010). Moreover, the findings add to the growing research on the impact of PKOs on violence that is often below the threshold of war and may not directly mimic the wartime cleavage (Autesserre, 2014;Bara, 2020;Fjelde and Smidt, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Specifically, investigating election-related activities helps us to understand how PKOs can secure political transitions after war and nuances general critiques of liberal peacekeeping (for an overview, see Paris, 2010). Moreover, the findings add to the growing research on the impact of PKOs on violence that is often below the threshold of war and may not directly mimic the wartime cleavage (Autesserre, 2014;Bara, 2020;Fjelde and Smidt, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have revealed the significant limitations of peacekeepers in curbing post-war violence that does not mimic the wartime master cleavage, such as crime or local power struggles (e.g. Autesserre, 2014; Bara, 2020; Di Salvatore, 2019). Thus, PKOs’ ability to reduce violence motivated by election dynamics could also be questioned.…”
Section: What We Know About Peacekeepers’ Effects In Electionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hultman et al, 2016). However, this effectiveness in altering the strategic environment in which actors operate may come with new and unforeseen challenges, such as an increase in criminal violence (Salvatore, 2019), or a shift toward different forms of violence or actors (Bara, 2020). Such shifts in the form and perpetrators of violence will remain invisible if we continue to primarily compare individual forms of violence to their absence, rather than to related forms of violence.…”
Section: Using the Framework For An Integrated Research Agendamentioning
confidence: 99%
“…He demonstrates that the UN Mission in Liberia (UNMIL)a peacekeeping force of over 16,000 military personnel, civilians and police officers, the goal of which was to monitor a ceasefire agreementsignificantly improved governance in that country. Mvukiyehe (2018) also examines UNMIL and finds that citizens were more likely to participate in national politics if they had interacted with this mission, suggesting that positive peacekeeping experiences may strengthen the rule of law (see also Bara 2020). Further research is needed to tease out the precise relationship between peacekeepers and good governance.…”
Section: Disaggregating and Expanding The Data On Peacekeepingmentioning
confidence: 99%